2020
DOI: 10.1111/jfpp.14993
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antioxidative activity of the essential oil and seed extracts of Artocarpus heterophyllus for effective shelf‐life enhancement of stored meat

Abstract: This study was designed to examine the in vitro antimicrobial and antioxidant activity of the essential oil and various extracts processed from Jackfruit seed (Artocarpus heterophyllus). Seed extracts obtained from Jackfruit were tested for TPC and TFC, and the TPC of 34.48 ± 1.77 mg GAE/g extract was detected while TFC of 0.19 ± 0.004 mg QE/g extract was found significantly. Phytochemical screening of A. heterophyllus seed extracts using UPLC–QTOF/MS revealed the presence of eight compounds, representing (−)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…A 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was based on the antioxidants scavenging ability towards the stable-free radical DPPH (Ramli et al, 2021). A total amount of 3 ml of 0.004% DPPH solution in methanol was added and mixed to 0.03 g of control and marinated meat.…”
Section: Dpph-free Radical Scavenging Activitymentioning
confidence: 99%
“…A 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was based on the antioxidants scavenging ability towards the stable-free radical DPPH (Ramli et al, 2021). A total amount of 3 ml of 0.004% DPPH solution in methanol was added and mixed to 0.03 g of control and marinated meat.…”
Section: Dpph-free Radical Scavenging Activitymentioning
confidence: 99%
“…Hence, ultraviolet light source, autoclaving and centrifugation are the different types of pre-treatment methods used to remove suspended solids and algae feeding organism such as protozoa and bacteria. Wastewater filtration and sterilization has also been carried out in many previous studies, although it has been shown that these treatments can sometime change the content of nutrients (Sawayama et al, 1992;and Ramli et al, 2020b).…”
Section: Removal Of Tp By Various Proportions Of C Vulgarismentioning
confidence: 99%
“…For removal of nutrients from wastewater, single strain or compound of microalgae along with bacteria growthpromoting microalgae are used (Sriram and Seenivasan, 2012). Wastewater samples were collected from secondary effluent of the wastewater treatment, before chlorination; so autoclaving was necessary to eliminate bacteria and pathogens (Ramli et al, 2020b). The Chlorella sp.…”
Section: Removal Of Tp By Various Proportions Of C Vulgarismentioning
confidence: 99%
“…Fruit waste is produced in significant numbers as a result of agricultural operations. Pineapple, jackfruit, citrus, banana, apple, and pear residues leftover from industrial processing are examples of such litter (Bhuyar, Maniam, et al., 2021; Ramli, Badrulzaman, et al, 2021; Ramli, Binti Muhammad Sukri, et al., 2021; Ramli et al, 2020). Bananas, apples, and pears produce around 107.1, 75.5, and 24.0 million tons per year, respectively, and 25%–40% of this mass is wasted after processing.…”
Section: Introductionmentioning
confidence: 99%